The cortical actin determines different susceptibility of naïve and memory CD4+ T cells to HIV-1 cell-to-cell transmission and infection. - Marc Permanyer (Public Library of Science (PLoS), 2013)
Memory CD4+ T cells are preferentially infected by HIV-1 compared to naïve cells. HIV-1 fusion and entry is a dynamic process in which the cytoskeleton plays an important role by allowing virion internalization and uncoating. Here, we evaluate the role of the cortical actin in cell-to-cell transfer of virus antigens and infection of target CD4+ T cells. Using different actin remodeling compounds we demonstrate that efficiency of HIV-internalization was proportional to the actin polymerization of the target cell. Naïve (CD45RA+) and memory (CD45RA-) CD4+ T cells could be phenotypically differentiated by the degree of cortical actin density and their capacity to capture virus. Thus, the higher cortical actin density of memory CD4+ T cells was associated to increased efficiency of HIV-antigen internalization and the establishment of a productive infection. Conversely, the lower cortical actin density in naïve CD4+ T cells restricted viral antigen transfer and consequently HIV-1 infection. In conclusion, the cortical actin density differentially affects the susceptibility to HIV-1 infection in naïve and memory CD4+ T cells by modulating the efficiency of HIV antigen internalization.